Análise do aproveitamento energético em redes de distribuição de água com a utilização de bombas como turbina (BFT) - SILVA, Victor Renan Barbosa da (Universidade Federal do Pará, 2024)
Climate change has intensified research related to the production of renewable energies around the world. In this sense, the present study intends to contribute to the analysis of the use of Pumps Functioning as Turbine (PAT) to replace Pressure Reducing Valves (PRV), aiming both at the control of pressure in water distribution networks, as well as , consequently, its use for energy generation. The installed PAT must be able to operate under different flow rates due to fluctuations in the water consumption rate, which makes it difficult to select the appropriate pump, therefore, the selection process of PATs to replace PRVs was optimized by combining two selection methods and PAT prediction, Williams (1995) the first method was used to select the appropriate PAT according to height and flow data available in the network, then the method of Rossi et al. (2019) was used to evaluate the characteristic curves of the pump as a turbine, with particular attention to out-of-design operating conditions. Two simulations were performed for the optimization process, considering the PAT with constant speed, applied to a real network that was divided into 3 district measurement areas (DMA). In the first simulation a PAT was added to the network to replace a PRV located at (DMA 3), in the second simulation two PATs were added to the network (DMA 3) to replace the PRVs. The results show, in simulation 2, that the pressure control was better, in addition to the recovery of electrical energy, which was 190.96 kWh/day or 69.70 MWh/year, corresponding to a reduction of 41.74 tons of CO2 not emitted. Thus, the energy recovery was 267% higher compared to simulation 1. In addition, the pressure control also presented satisfactory results, staying within the established standards. Therefore, the combination of Williams' (1995) and Rossi et al. (2019), simplified the work of BFT selection and prediction with significant results and it was possible to conclude that BFTs working at peak consumption hours can adjust the required standard pressure and, in the rest, PRVs can regulate the pressure. In this case, in addition to controlling the pressure continuously, significant renewable energy can be recovered from the WDN